2018
DOI: 10.1016/j.anireprosci.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunization against bone morphogenetic protein-15 and growth differentiation factor-9 on ovarian function in mares

Abstract: Currently there is no contraceptive vaccine that can cause permanent sterility in mares. This study investigates the effect of vaccination against oocyte-specific growth factors, Bone Morphogenetic Protein 15 (BMP-15) and Growth Differentiation Factor 9 (GDF-9), on ovarian function of mares. It was hypothesized that immunization against these growth factors would prevent ovulation and/or accelerate depletion of the oocyte reserve. For this study, 30 mares were randomly assigned to three groups (n = 10/group) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…On the other hand, immunization against these proteins for prolonged periods caused a block in follicular development ( McNatty et al, 2007 ). These results are different from those obtained in mares, in which immunization against GDF9 did not affect ovulation rate, but decreased preovulatory follicle diameter and estrus manifestation, while immunization against BMP15 negatively affected ovulatory rate and resulted in luteinization/ovulation of small follicles ( Davis et al, 2018 ).…”
Section: Transforming Growth Factors: Major Players In the Local Cont...contrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, immunization against these proteins for prolonged periods caused a block in follicular development ( McNatty et al, 2007 ). These results are different from those obtained in mares, in which immunization against GDF9 did not affect ovulation rate, but decreased preovulatory follicle diameter and estrus manifestation, while immunization against BMP15 negatively affected ovulatory rate and resulted in luteinization/ovulation of small follicles ( Davis et al, 2018 ).…”
Section: Transforming Growth Factors: Major Players In the Local Cont...contrasting
confidence: 99%
“…Thus, interest in understanding the role of these factors in mammalian ovarian and reproductive physiology has increased in recent decades. In addition, studies demonstrate that the manipulation of TGFs can be applied in techniques to control the estrous cycle in different species such as sheep, cattle, horses, and deer ( Galloway et al, 2000 ; Hanrahan et al, 2004 ; Juengel et al, 2009 ; Davis et al, 2018 ).…”
Section: Transforming Growth Factors: Major Players In the Local Cont...mentioning
confidence: 99%
“…BMP15 and GDF9 are the important oocyte-secreted factor (OSF) that regulate the cumulus development to nurse itself [26]. Recent study in the mare showed that immunization against BMP15 and GDF9 induces a lower ovulation rate and been proposed as one kind of contraceptive [27]. Therefore, BMP15 and GDF9 may have some good in uence on mare follicle and oocyte development.…”
Section: Bmpr1 Bmpr2 and Alkmentioning
confidence: 99%
“…Although studies on GDF-9 have been conducted on various animal species such as laboratory animals (McPherron et al 1993, McGrath et al 1995, Dong et al 1996, Elvin et al 1999, ruminants (Bodensteiner et al 1999, Hanrahan et al 2004, Hu et al 2010, Polat et al 2015, Tang et al 2018, mares (Dal et al 2013, Davis et al 2018, Stefaniuk-Szmukier et al 2018, and bitches (Fernandez et al 2016, studies on cats are very limited. In a study examining the TGF-β superfamily members through immunohistochemical methods in feline ovarian tissue, GDF-9 is reported to be a potent growth factor in follicle maturation (Bristol et al 2004).…”
Section: Introductionmentioning
confidence: 99%